(untitled) (Research, Society and Development, 2022)
The novel coronavirus (SARS-CoV-2), responsible for the COVID-19 pandemic, causes a respiratory infection disease of rapid transmission through droplets in the air, from person to person, or by contact with contaminated surfaces. Infected people can be asymptomatic or symptomatic, with symptoms like pneumonia, which can lead to hospitalization of these patients. The role of speech therapists in the multiprofessional team has been extremely important in dealing with the pandemic, especially in symptomatic and intubated patients. After extubation, these patients can be affected by serious speech-language pathology consequences, requiring follow-up for rehabilitation with a speech-language therapist. Thus, the aim of this study was to carry out, in an unprecedented way, a review in the literature about the consequences of COVID-19 in the major areas of speech therapy. To meet this objective, a narrative review was carried out, from which it was possible to analyze the major areas of speech therapy in which patients had consequences during or after the COVID-19 infection, such as difficulties in swallowing (dysphagia), tracheostomy, tinnitus, hearing loss, language, and speech delay. It was also possible to present the importance of telephonoaudiology to accompanying patients. Given the above, from the data of this review, it was possible to observe that most of the consequences associated with COVID-19 dealt with the same context: after or during the period of infection, where patients were affected by speech-language pathology consequences which required intervention to assess, rehabilitate and, when necessary, apply appropriate therapy. Furthermore, future investigations, such as randomized clinical trials, are encouraged to better elucidate these consequences, since some information is still found in studies with low scientific evidence such as case reports.